PENGARUH KEPERCAYAAN, KEMUDAHAN, HARGA DAN KUALITAS INFORMASI PENGGUNAAN E-COMMECE TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA SITUS BUKALAPAK.COM (Studi Pada Mahasiswa S1 Fak.Ekonomi Unisma Angkatan 2013) - Ismail Hidayat; Rois Arifin; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis research aims to analyze the influence of confidence, convenience, price, and quality of the information against the purchasing decision partially and simultaneous. Type of this research is quantitative research. The respondents in this study was a student of economic faculty of Islamic University of Malang by 2013. The sample used in this study the student is a student of economic faculty of Islamic University of Malang ever making a purchase on the site bukalapak.com a number of 37 students. The data collection method used is to disseminate the questionnaire and interview. The results showed that the confidence and ease of influence on purchasing decisions in partial. Whereas the prices and the quality of the information does not affect purchasing decision partially. Simultaneously variable trust, convenience, price, and quality of information influence on purchasing decisions.Keywords: Trust, convenience, price, quality of information, purchase decision